Formulation of Diclofenac Sodium Emulsion Using Colocynthis Citrullus L. (Melon) Seed Oil (2019)
Background: Melon seed obtained from the fruit of Colocynthis citrullus L. is widely used in Nigeria as a soup thickener. The seed has a high oil yield (42-57%) which has been largely unexplored as excipient in pharmaceutical formulations. Objectives: To evaluate melon seed oil as a drug carrier in emulsion using diclofenac as a model drug. Methods: Melon seed oil was extracted and the physicochemical properties were characterised. The emulsions were prepared using the traditional wet and dry gum methods, and all the emulsions were evaluated using viscosity measurements, creaming rate, and in-vitro drug release. Results: Melon seed oil had a pale yellow colour, with characteristic taste, and a neutral pH. Melon seed oil exhibited higher acid, saponification and ester values than castor oil but lower iodine value indicating an edible non-drying oil, unsusceptible to auto-oxidation. Both oils achieved a great degree of emulsification with globule size < 15mm μm. Emulsions of melon seed oil were generally less viscous with a higher degree of creaming compared to castor oil emulsions. Diclofenac emulsions prepared with melon seed oil, however, were more viscous and gave the highest release of diclofenac irrespective of the method of preparation. Only diclofenac emulsion prepared with melon seed oil using the wet gum method had > 70 % release within 45 minutes thus meeting the official specification. Conclusion: Melon seed oil functioned as a drug carrier for diclofenac. Thus, it will find application in pharmaceutical emulsions.